Pendulum at Rest Monopole Antenna (Analysis of the Complex Physical System Pendulum at Rest) - Crivoi, Dumitru; Rediu, Maria (European Journal of Applied Sciences, 2024)
Background: Unexpected results (anomalies) contain essential information regarding the physical consistency of the tested system ("test body") respectively, regarding the physical consistency of the paradigm used to construct the experiment, collect data and analyze measurement results. Based on the priori information and the own information accumulated, in order to facilitate the theoretical and experimental analysis, the complex physical pendulum model composed of three subsystems was adopted, namely: the subsystem of electrical parameters of the environment S1, the subsystem of the mechanical pendulum itself S2 respectively, the disturbing subsystem of celestial bodies S3. Aims: Highlighting nongravitational perturbations of the pendulum at rest. Method(s): The representation in the form of a physical complex system by describing the processes with the help of physical laws (balance sheet equations) and experimentally. Results. A new model of the complex physical system of the pendulum at rest (antenna) and a modern gravitational-electrical paradigm (Mach-Maxwell paradigm) for experiment construction, data collection and analysis of results, respectively Conclusions: The optimal physical consistency of the new paradigm of experiment construction, data collection and analysis of measurement results allows highlighting nongravitational perturbations of the pendulum at rest.